Population fluctuation of Diaphorina citri Kuwayama (Hemiptera: Liviidae) and survey of some natural enemies in Ecuador - Chavez, Y.; Castro, C.; González, Guillermo F.; Castro, Jessenia; Peñarrieta Bravo, Soraya; Perez-Almeida, Iris; Chirinos, Dorys Terezinha; Kondo Rodríguez, Demian Takumasa (Ediciones INTA, 2019)
Diaphorina citri detected in Ecuador for the first time in 2013, is an insect pest of global relevance. It is the main vector of the phloem-limited bacterium Candidatus Liberibacter asiaticus, the causal agent of Huanglongbing (HLB), a devastating disease of citrus trees. During the period from April 2016 - July 2017, population fluctuation studies and a search for natural enemies of D. citri were conducted on young shoots of orange jessamine, Murraya paniculata, and Citrus spp. The natural enemies of D. citri were collected in the Provinces of Guayas and Santa Elena, Ecuador. A total of 1660 specimens of predators belonging to five species were collected, consisting of three coccinellids, Cheilomenes sexmaculata, the most abundant species (39.9%, P <0.05), followed by Cycloneda sanguinea (15.8%), and Paraneda pallidula guticollis (4.1%) (Coleoptera: Coccinellidae), an assassin bug, Zelus sp. (Hemiptera: Reduviidae) (17.8%), and the lacewing Ceraeochrysa sp. (Neuroptera: Chrysopidae) (22.4%). The parasitoid wasp Tamarixia radiata also was found, reaching a parasitization rate of 90% of the psyllid nymphs. This study represents the first report of P. pallidula guticollis feeding on D. citri. The diversity of natural enemies and the high level of parasitism detected suggest the importance of natural enemies as biological control agents of this important phytophagous insect pest. The natural control by these beneficial insects would make unnecessary the applications of chemical insecticides that are carried out in Ecuador for the control of this insect, especially at this moment when the HLB causing bacterium has not been reported in Ecuador.